2014
DOI: 10.1128/jb.02413-14
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Host Iron Sources by Corynebacterium diphtheriae: Multiple Hemoglobin-Binding Proteins Are Essential for the Use of Iron from the Hemoglobin-Haptoglobin Complex

Abstract: The use of hemin iron by Corynebacterium diphtheriae requires the DtxR-and iron-regulated ABC hemin transporter HmuTUV and the secreted Hb-binding protein HtaA. We recently described two surface anchored proteins, ChtA and ChtC, which also bind hemin and Hb. ChtA and ChtC share structural similarities to HtaA; however, a function for ChtA and ChtC was not determined. In this study, we identified additional host iron sources that are utilized by C. diphtheriae. We show that several C. diphtheriae strains use th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
40
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 38 publications
0
40
0
Order By: Relevance
“…It appears that these heme-binding proteins serve redundant functions, and as such, a mutant lacking both HtaB and ChtB is deficient at utilizing Hb as an iron source [152]. Recently, it has been shown that ChtA and ChtC are both capable of binding Hp–Hb for heme extraction, and acquisition of heme from Hp–Hb requires HtaA [153]. The current model (Fig.…”
Section: Gram-positive Heme Acquisition Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…It appears that these heme-binding proteins serve redundant functions, and as such, a mutant lacking both HtaB and ChtB is deficient at utilizing Hb as an iron source [152]. Recently, it has been shown that ChtA and ChtC are both capable of binding Hp–Hb for heme extraction, and acquisition of heme from Hp–Hb requires HtaA [153]. The current model (Fig.…”
Section: Gram-positive Heme Acquisition Strategiesmentioning
confidence: 99%
“…The current model (Fig. 2) for Hp–Hb heme acquisition involves binding of Hp–Hb by a combination of HtaA and ChtA or ChtC, heme extraction either actively or passively, and transfer to HtaB, HmuT, and HmuUV [153]. …”
Section: Gram-positive Heme Acquisition Strategiesmentioning
confidence: 99%
“…C. diphtheriae, in particular, acquires heme iron by utilizing the HmuTUV and HtaA heme transport system (9)(10)(11). Upon entering the cytosol, the heme moiety is degraded by the heme oxygenase HmuO, causing the release of the heme-associated iron (12,13).…”
mentioning
confidence: 99%
“…Analysis of the full genome sequence [2] is consistent with a number of iron uptake systems in this organism. The iron and heme transporter systems are predicted to be coordinately expressed with the toxin [4–7]. This, along with the iron requirement for virulence, suggests that iron acquisition is a key component for pathogenicity.…”
Section: Introductionmentioning
confidence: 99%
“…The hmu gene cluster comprises two heme-binding surface-anchored proteins, HtaA and HtaB, along with a heme binding lipoprotein (HmuT) and an ABC-type heme transporter (HmuUV) [7, 3639] (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%